Street Children-A Vulnerable Section of Society: Understanding the Challenges Faced by Street Children (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this 21stcentury we have been encountering various kinds of problems. The issue of Streetchildren is one of them: a vulnerable section of society. Thesechildren are commonly seen when we stop near traffic signals and when theyapproach people with different needs, some for begging and some for sellingtheir prepared items.